Investigations on the safe stroke of mechanical HVDC vacuum circuit breaker - Ning Xia; Jiyan Zou; Deshi Liang; Yang Gao; Zhihui Huang; Yongxing Wang (The Journal of Engineering, 2019)
Here, a DC vacuum arc interruption test based on the hybrid high-speed actuator and the method of commutation is carried out in the synthetic loop system. The safe stroke is one of the basic breaking parameters. The minimum safe stroke directly determines the commutation time and breaking property of the mechanical DC vacuum circuit breaker. The main circuit breaker is a high-speed vacuum switch driven by electromagnetic repulsion actuator. In order to simplify its control system, the commutation switch also adopts high-speed vacuum switch. The main current source for verification test of this DC breaker system is provided by a LC oscillator circuit with lower frequency. Simulations with some experiments were completed on breaking process of this system by PSCAD. The breaking current is 4 kA by the DC breaker system proposed here, the opening speed is about 2.417 m/s in this experimental system; From the results, the simulation and experimental waveforms are compared and analysed, and some effects on safe stroke of the DC vacuum circuit breaker is studied. The shortest arcing time is about 0.89 ms and the minimum safe stroke is about 2.15 mm under the lower voltages.